Transient pressure wave in the behind armor blunt trauma: experimental and computational investigation. Issue 3 (17th February 2017) - Luo, Shaomin; Xu, Cheng; Wang, Shu; Wen, Yaoke
Abstract: In the last few decades, various researches focus on the transient pressure in the behind armor blunt trauma. This paper presented a investigation on the transient pressure in the ballistic gelatin behind a soft body armor subjected to the impacting from three ammunitions. Experimental results show that three peaks appear on the pressure–time curves without taking into account the ammunition type and the impact velocity. Furthermore, numerical models of the test were created to compare modelling results to the pressure from the pressure gauges buried in the gelatin block. The main features on the pressure–time cure were discussed to analyze the wave formation and propagation. With the verified model, the effect of the boundary was also investigated to explain the wave reflection which appeared after two peaks.